Model-based fed-batch cultivation of Viola odorata plant cells exhibiting antimalarial and anticancer activity - Babu, R.; Veeramani, Manokaran; Aadinath, Wallepure; Muthuvijayan, Vignesh; Singh, Shailja; Srivastava, Smita (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionViola odorata is a medicinal plant used in the indigenous systems of medicine in India, to treat respiratory tract disorders. V. odorata natural plant source is limited in availability. Bioprocess principles can be applied to develop sustainable methods for the commercial production of high-quality V. odorata plant biomass.MethodsTo this effect, the in vitro culture conditions of V. odorata were rationally optimized to increase the biomass production up to 21.7 ± 0.8 g DW L−1 in 12 days in shake flasks. In the current study, a modified stirred tank reactor and a balloon-type bubble column reactor were used to improve the biomass production at the batch reactor level. Sufficient nutrient feeding strategies were developed using first principle-based mathematical modelling to overcome substrate inhibition and achieve higher cell density in the reactor. In addition, bioreactor-cultivated biomass extracts (aqueous/alcoholic) were tested for various bioactivities like hemolytic, cytotoxic, anti-inflammatory, and antiplasmodial.ResultsExperimental validation of the fed-batch model-predicted strategy resulted in a two-fold enhancement in biomass production (32.2 g DW L−1) at the bioreactor level. Biomass extracts showed no hemolytic activity up to 4 mg mL−1 concentrations. Further, the stirred tank cultivated biomass extract displayed cytotoxicity against Caco2 - colon carcinoma cell lines, exhibiting an IC50 of 1.5 ± 0.1 mg mL−1. In vitro experiments also indicated the anti-inflammatory property in the bioreactor cultivated plant biomass extracts. As a new application, the biomass extracts also demonstrated up to 80% inhibition of malarial parasite growth in vitro. Additionally, when administered alongside artesunate (1.8 mg kg−1d−1), the plant extracts (400 mg kg−1d−1) effectively controlled parasite growth in vivo.DiscussionIt is to be noted that a first report on fed-batch cultivation of V. odorata cell suspension culture in lab-scale bioreactors and on the antiplasmodial activity of the V. odorata plant extracts. Overall, the bioactive potential of the in vitro-generated plant biomass extracts is similar to that in the natural plant biomass extracts.